Pengaruh Variasi Diameter Pipa Cabang Terhadap Koefisien Kerugian Pada Pemisahan Aliran - Musrady Mulyadi (Jurnal Teknik Mesin Sinergi, 2012)
The research aimed to investigate: (1) the influence of flow rate ratio of loss coefficient (k) at the branch pipe with angle 450, (2) the value of the local loss coefficient (k) that occurs in the branch pipe diameter variations (branch) at, ½, ¾, 1, 1 ¼, and 1 ½ inch, then straight pipe with a diameter 2 inches, and (3) the effect of changing ratio between branch diameter pipe and a straight pipe to the loss coefficient (k) on the pipe branch. The research was conducted with a form of experiment, namely the dividing flow in a 45 Tee Junction with variation diameter PVC pipe. After that it was calculated the local coefficient of losses incurred by changes discharge ratio of 0.0 to 1. The results reveal that the increasing of flow ratio with a variation branch pipe diameter increase the total loss coefficient, Ktotal. Discharge ratio 0.0 to 1,the value of the local loss coefficient from the main to the branch of K3-1 in ½ inch diameter branch pipe 1.11 until 7.29, ¾ inch diameter 1.17 until 2.85, 1 inch diameter of 1.07 to 1.82, 1¼ inch diameter 1.08 until 1.40 and ½ inch diameter 1.02 to 0.92, while the local loss coefficient related to the flow in the main of K3-2 range from 0.04 until 0.48 for all variations of the branch pipe diameter. The smaller ratio of the diameter of the branch pipes with the main pipe will increase the value of the total losses coefficient.